Proposed Knowledge Management System to Improve Corporate Digital Learning Development Project in PT X - Budi Kristanto; Jann Hidajat Tjakraatmadja; Rudy Bekti (Inovbiz: Jurnal Inovasi Bisnis, 2023)
Digital learning has become one of the effective methods to improve learners' knowledge and skills, especially in the current digital era that is rapidly developing. PT X, as a digital learning solution provider in Indonesia, sees that optimizing production in corporate digital learning development projects is very necessary at this time. The rapidly changing character of digital business, the complexity of the project process, and the large amount of learning material from clients with various backgrounds in industries require a knowledge management approach to improve it. This research begins by assessing the readiness of knowledge management in PT X using Asian Productivity Organization (APO) Knowledge Management Tools and semi-structured interviews. The implementation of knowledge management is presented in a design to form four organizational enablers and KM initiatives complete with their implementation schedules.